A Scale of Atomic Electronegativity Based on Floating Spherical Gaussian Orbital Approach. Issue 22 (14th June 2021) - Tandon, Hiteshi; Labarca, Martín; Chakraborty, Tanmoy
Abstract: Electronegativity ( χ ) is an old yet valuable concept having multidisciplinary applications. To advance the understanding of this concept, an electronegativity model has been proposed based on polarizability within the context of Floating Spherical Gaussian Orbital (FSGO) approach. The model provides atomic electronegativity scale for 120 elements. The calculated electronegativity presents marked periodicity and relates well with other electronegativity scales. Further, Electronegativity Equalization Principle is validated by the computed electronegativity data. The proposed scale has also been successfully applied to compute Fermi energy for some metal oxides. In accordance with the literature, this is the first FSGO‐polarizability based model of electronegativity. Abstract : The study proposes an empirical model based on floating spherical Gaussian orbital approach that allows calculation for atomic electronegativity for 120 elements of the periodic table based on polarizability.